Theory Of Reasoned Action sebagai Lensa untuk Memahami Faktor Penentu Kepatuhan Pajak WPOP Non-Karyawan - Ni Made Nuriasih; I Nyoman Putra Yasa; Putu Yunartha Pradnyana Putra (Lembaga Pengembangan Kinerja Dosen, 2025)
Tax compliance among non-employee individual taxpayers (WPOP) remains a significant challenge in Indonesia, even after the implementation of the 0.5% final income tax rate aimed at simplifying tax administration and reducing the fiscal burden. This study seeks to examine the determinants of WPOP tax compliance by applying the Theory of Reasoned Action (TRA) as the primary conceptual framework. The research employed a qualitative literature review approach, analyzing scientific articles from national and international journals, academic books, and official taxation reports published between 2015 and 2025. The findings indicate that the final tax policy provides structural incentives, however, its effectiveness is largely dependent on taxpayers' internal factors such as motivation, awareness, and perception of fairness. Accounting literacy plays a role in improving the accuracy of tax recording, calculation, and reporting, yet it does not consistently translate into higher compliance without being reinforced by positive attitudes and supportive social norms. Psychological factors such as trust in tax authorities, perceived justice, and the influence of social environments are shown to be more consistent in shaping attitudes and subjective norms, which in turn strengthen compliance intentions in accordance with TRA. These findings suggest that WPOP tax compliancecannot be adequately understood from structural or technical aspects alone but must be addressed in an integrative manner that incorporates fiscal policies, technical capacity, and psychological dimensions. The implication is that voluntary tax compliance can be fostered through integrative strategies combining simplified tax rates, taxpayer education programs, and greater transparency in public fund management. Future studies are recommended to conduct large-scale quantitative and comparative analyses across sectors and regions to validate these conceptual insights and strengthen their generalizability.